2022
DOI: 10.1111/jrh.12667
|View full text |Cite
|
Sign up to set email alerts
|

Rural and urban differences in perceptions, behaviors, and health care disruptions during the COVID‐19 pandemic

Abstract: Purpose The objective of this study was to assess perceptions, health behaviors, and disruptions related to the COVID‐19 pandemic in a largely rural, Midwestern state, and to examine differences between rural and urban respondents. Methods A questionnaire was mailed August 2020 to a sample of 10,009 registered voters in Iowa ages 18‐100 years, with oversampling from 6 select rural counties. Previously validated and tested items assessed COVID‐19 precautions, health care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“… 43 Meanwhile, a US study reported that the proportion of people with increased body weight during the COVID-19 outbreak was higher in urban areas than in rural areas. 44 Further studies are required to clarify the differences in the effects of COVID-19 on obesity and obesity-related comorbidities between rural and urban areas.…”
Section: Discussionmentioning
confidence: 99%
“… 43 Meanwhile, a US study reported that the proportion of people with increased body weight during the COVID-19 outbreak was higher in urban areas than in rural areas. 44 Further studies are required to clarify the differences in the effects of COVID-19 on obesity and obesity-related comorbidities between rural and urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our findings may reflect urban and rural population differences in the perception and/or enforcement of COVID‐19 policies such as lockdown and social distancing policies (Jiang et al, 2022). Evidence suggests that rural populations were less likely to perceive COVID‐19 to be a serious threat, and as such less likely to remain motivated to adhere to lockdown and social distancing policies than their urban counterparts (Greteman et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…First, in order to maintain comparability to the (unweighted) cancer patient sample, we did not weight our general population sample for this analysis. As a result, our general population sample over-represents rural residents [29]. Additionally, the 26% response of our cancer patient survey increases risk for nonresponse bias.…”
Section: Discussionmentioning
confidence: 99%
“…Methods and measures pertaining to the general population survey have been described in detail elsewhere [29]. Briefly, in August 2020, we mailed the general population survey to a random sample of 10,009 Iowans from the 2018 Iowa voter registration file.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation